Covid-19: How India fared during lockdown - Boss, Ruchira; Roy, Devesh; Saroj, Sunil; Pradhan, Mamata (Financial Express, 2021)
Possibly even more than a public health crisis, Covid-19 is an economic crisis manifested most severely in the labour market. In the face of the pandemic, the structure of the labour market typifies the extreme vulnerability of workers in India. With Covid-19 and the resultant lockdowns, there has been a significant discourse on employment, although often without relevant and representative data.